Humans or machines? scientific determinism within the context of Yoruba human ontology (2022)
Freewill has been a subject of intense study in the history of philosophy, this revolves around the debate that are humans free or are their actions determined? While there has been a lot of questions on the nature of human will, the search for answers remains relevant in contemporary studies as seen in the entrance of neuroscience to this quest. Neuroscience, in the study of the human will arrived at a conclusion based on empirical studies that freewill is an illusion because the human will is determined by cerebral activities. The discovery in the field of neuroscience therefore challenges the traditional belief about freewill and our beliefs that humans are in full control of their will. This submission indicated that human decisions for actions were initiated before humans became aware of them, that is, likening humans to machines, thereby creating a lacuna especially within the Yoruba religious and cultural contexts. This study therefore, interrogated the position of neuroscience on the human will by focusing on how scientific determinism can be viewed from the Yoruba worldview. Scientific determinism evident in the field of neuroscience was examined with a view to situating the findings of neuroscience on human will within the context of Yoruba human ontology.